2016
DOI: 10.1123/japa.2015-0178
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of activPAL and activPAL3 Accelerometers in Older Adults

Abstract: The aim of this study was to assess concurrent validity between activPAL and activPAL3 accelerometers in a sample of 53 community-dwelling older adults ≥ 65 years. Physical activity (PA) was measured simultaneously with activPAL and activPAL3 while performing scripted activities. The level of agreement between both devices was calculated for sitting/lying, standing, and walking. In addition, PA was measured over one week using activPAL to estimate the expected agreement with activPAL3 in real life. Overall agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The activPAL3 monitor has only had direct validation in adults aged 18–65 years and children aged 6–17 years [30]. However, the previous activPAL model has been validated in older adults [56], and studies have shown that there is strong agreement between both models in both older adults [57] and in adults and children [58]. We are thus confident that the activPAL3 is valid for use in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The activPAL3 monitor has only had direct validation in adults aged 18–65 years and children aged 6–17 years [30]. However, the previous activPAL model has been validated in older adults [56], and studies have shown that there is strong agreement between both models in both older adults [57] and in adults and children [58]. We are thus confident that the activPAL3 is valid for use in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Filtering and choice of epoch time must be set before data collection. Actical (Mini Mitter Respironics, Inc., Bend, OR, USA) [ 37 ] Waist ‘Omni-directional’ accelerometer using piezoresistive and capacitive technology; most sensitive to motion in one plane Activity counts that are filtered and digitized from acceleration signals activPAL (PAL Technologies Ltd., Glasgow, Scotland) [ 38 ] Thigh Uniaxis accelerometer using capacitive technology Classifies activities as sitting/lying, standing or walking activPAL3 (PAL Technologies Ltd., Glasgow, Scotland) [ 38 ] Thigh Triaxis accelerometer using capacitive technology Classifies activities as sitting/lying, standing or walking GENEActiv (Activinsights Ltd., Kimbolton, UK) [ 39 ] Thigh Triaxis accelerometer with a near-body temperature sensor Raw-mode data allows for open-source post-data collection filtering MotionWatch8 (CamNtech, Cambridge, UK) [ 40 ] Wrist Triaxis accelerometer using MEMs technology, with ambient light sensor Activity counts from acceleration signals in a single axis only or in vertical magnitude using epoch-based recoding that uses the three axis; raw-mode data allows for post-data collection filtering Note: Triaxial accelerometers measure acceleration in vertical axis, antero-posterior and medio-lateral …”
Section: Resultsmentioning
confidence: 99%
“…The Actical study [ 37 ], the largest of the four, included 200 participants with a mean age of 64 years. The ActivPAL3 study [ 38 ] included 53 participants with a mean age of 75 years. The GENEActiv study [ 39 ] included 40 participants with a mean age of 74 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…StS) were recorded with an ActivPAL (PALtechnologies, Glasgow, UK) physical activity monitor which was attached to each participant's thigh (dominant side) for 48 hours. This sensor has been validated in a wide range of populations including older people [18].…”
Section: Secondary Outcome Measurementioning
confidence: 99%